Local Graph Embedding Based on Maximum Margin Criterion (LGE/MMC) for Face Recognition - Wan, M.; Gai, S.; Shao, J. (Informatica)
Local Graph Embedding Based on Maximum Margin Criterion (LGE/MMC) for Face Recognition